Goods follow bytes: The impact of ICT on EU trade - Anselm Mattes; Philipp Meinen; Ferdinand Pavel (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper empirically assesses whether the deployment and use of Information and Communication Technology (ICT) infrastructure at the national level affects trade flows within the European Union (EU) and between the EU and its main trading partners. The analysis tests the hypothesis that availability and use of ICT enhances trade by reducing transaction costs and through network effects that materialize when both trading partners are advanced users of ICT. The empirical analysis is based on the application of gravity equations in various robust specifications. The results suggest that ICT does have a significant impact on EU trade. In particular, we find trade to be enhanced if both trading partners reveal advanced ICT endowments, which supports the expected network effects. Additionally, we observe trade diversion effects from less to highly ICT developed countries.
Keywords: F1; D2; 330; Exports; ICT; gravity model; international trade; network effects